2020
DOI: 10.7554/elife.63205
|View full text |Cite
|
Sign up to set email alerts
|

SlitC-PlexinA1 mediates iterative inhibition for orderly passage of spinal commissural axons through the floor plate

Abstract: Spinal commissural axon navigation across the midline in the floor plate requires repulsive forces from local Slit repellents. The long-held view is that Slits push growth cones forward and prevent them from turning back once they became sensitized to these cues after midline crossing. We analyzed with fluorescent reporters Slits distribution and FP glia morphology. We observed clusters of Slit-N and Slit-C fragments decorating a complex architecture of glial basal process ramifications. We found that PC2 prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…To make sure that spinal cord patterning was maintained and that floor plate functions were preserved, we performed HCR RNA-FISH on E4 operated embryos. Consistently with the fact that ex vivo spinal cord open-books can be used to study DIN axon navigation across the floor plate 61,62 , we showed that the surgical manipulation did not interfere with expression of key guidance molecules such as Slit2 or neuron specification such as Isl1 expression (Figure 4d-e). As expected, Isl1 expression was still detected in a dorsal population of neurons (Figure 4d-e).…”
Section: Resultssupporting
confidence: 83%
“…To make sure that spinal cord patterning was maintained and that floor plate functions were preserved, we performed HCR RNA-FISH on E4 operated embryos. Consistently with the fact that ex vivo spinal cord open-books can be used to study DIN axon navigation across the floor plate 61,62 , we showed that the surgical manipulation did not interfere with expression of key guidance molecules such as Slit2 or neuron specification such as Isl1 expression (Figure 4d-e). As expected, Isl1 expression was still detected in a dorsal population of neurons (Figure 4d-e).…”
Section: Resultssupporting
confidence: 83%
“…As expected, in the spinal cord, GFP positive axons of the dorsal interneurons were observed to cross the midline below the soma layer of the floor plate that strongly expresses SLIT2 (Fig. 4 c) [ 64 ]. The resolution even allowed us to observe the individual axons navigating across the floor plate (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Yet, in contrast to regulators of fate specification and migration of glial cells, mechanisms driving their morphogenesis remain even more understudied. And yet this architecture may be key for axon pathfinding, either through physical interactions of adhesion or by presenting specific subcellular localization of membrane-bound guidance factors, such as the aforementioned Slit and Semaphorin3B clusters on endfeet of radial glial cells in the developing mouse spinal cord ( Ducuing et al, 2020 ). Thus, studying how astroglial cells establish their morphological cell architecture should be another important forefront in the investigations of neuropil development and axon navigation.…”
Section: Discussionmentioning
confidence: 99%
“…Growth cones establish contact with these glial cell surfaces during midline crossing. The clusters of Slit and Semaphorin3B fragments on these endfeet produce constraints protecting the growth cones from the risk of aberrant deviations due to active exploration of other cues in their environment ( Ducuing et al, 2020 ).…”
Section: Axon Guidance By Astroglia: Insights From the Chickmentioning
confidence: 99%